Effect of a multifaceted stewardship intervention on antibiotic prescribing and outcomes for acute bacterial skin and skin structure infections. (November 2018) - Roshdy, Danya; Jaffa, Rupal; Pillinger, Kelly E.; Guffey, Josh; Rozario, Nigel; Davidson, Lisa; McCurdy, Lewis
Background: Acute bacterial skin and skin structure infections (ABSSSI) are a leading cause of hospitalization, but are often treated inappropriately in the inpatient setting. A multifaceted stewardship intervention was implemented to encourage prescribing of guideline-concordant therapy (GCT). Objective: To examine the impact of this initiative on antimicrobial prescribing practices and patient outcomes. Methods: This was a single-center, retrospective study of adult inpatients admitted with a primary or secondary diagnosis of ABSSSI, classified by type and severity based on signs of systemic infection. Patients treated during the pre-intervention period (pre-IP) were compared with patients treated during the post-intervention period (post-IP). The primary endpoint was receipt of GCT. Secondary endpoints included receipt of anti-anaerobic antibiotic (AAA) or broad-spectrum antibiotics (BSA). Results: A total of 125 patients were included, 64 in the pre-IP and 61 in the post-IP. There was a statistically significant increase in prescribing of GCT during the post-IP compared with the pre-IP (14% versus 56%, p < 0.0001) and a decrease in use of AAA (56% versus 34%, p = 0.01). No difference was observed with use of BSA (16% versus 15%, p = 0.89). Use of the computerized order set during the post-IP was low (18%). There was a numerical, but non-significant reduction in 30-day readmission (14.1% versus 6.6%, p = 0.17). Conclusion: The multifaceted intervention was effective for improving prescribing of GCT for ABSSSI. Given low use of the computerized order set, improved prescribing seemed to be driven by provider education. Strategies around ongoing education may be key to sustain positive results of stewardship interventions.